Development and calibration of an integrative passive sampler for monitoring vinyl chloride monomer in drinking water networks. Issue 8 (1st July 2022) - Alembik, L.; Mazzella, N.; Hemion, T.; Husson, A.; Le Gat, Y.; Gilbert, D.
Abstract : This paper evaluates the applicability of a new sampling device for monitoring vinyl chloride monomer (VCM) in drinking water networks. Abstract : This paper evaluates the applicability of a new sampling device for monitoring vinyl chloride monomer (VCM) in drinking water networks. This device consists of an adsorbing cartridge filled with a strong adsorbent enclosed between two sheets of polyethylene–polyamide membrane. The passive sampler (PS) combines preconcentration on the cartridge with easy extraction by thermal desorption into a gas chromatograph (GC), coupled with a tandem mass spectrometer (MS/MS). In order to estimate the suitability of the device for monitoring VCM, samplers were calibrated in a hydraulic pilot under controlled parameters. The influences of temperature, flow velocity and variation of exposure concentration were then examined. Linear uptake was observed during a VCM exposure of 12 days and the effect of temperature on the sampling rate was evaluated. This sampling device responds to an aquatic environmental contamination and public health issue. Indeed, it combines the monitoring of an organic volatile contaminant dissolved in water and a sampling approach, which still is rarely used in drinking water networks. It offers complementary monitoring to current techniques, providing a more representative assessment of temporal contamination.